Pendekatan Pembelajaran untuk Mengoptimalkan Hasil TOEFL Listening - Arya Farlan Ananda; Siti Mahdiyani; Yadira Rizka Aulia; Aulia Mayada; Muhamad Alvin Najmi; Fadullah Rusadi; Syahrul Adam (INDO PUBLISHING, 2025)
This study examines effective learning approaches to optimize TOEFL Listening results through comprehensive analysis of various contemporary learning strategies and methods. TOEFL iBT Listening is a crucial component that tests participants' ability to understand academic conversations and university lectures with high complexity levels. The main challenges faced by test-takers include listening anxiety, heavy cognitive load, and lack of appropriate learning strategies. This article analyzes learning approaches based on second language acquisition theories, including Cognitive Load Theory, Schema Theory, and Input Processing Theory. The discussion encompasses cognitive strategies that integrate top-down and bottom-up processing, technology utilization through Mobile-Assisted Language Learning (MALL), and implementation of blended learning combining synchronous and asynchronous sessions. Research indicates that collaborative approaches and multimodal resource utilization are effective in reducing listening anxiety. Structured note-taking techniques, systematic academic vocabulary development, and continuous assessment systems have proven to significantly enhance listening abilities. Integration with other language skills creates synergistic effects benefiting overall language proficiency. The findings of this research provide practical contributions for educators and TOEFL test-takers in designing comprehensive and effective learning programs to achieve optimal results in the TOEFL Listening section.